Respostas
respondido por:
7
a₁=-3
a₄=24=-3*q³
q³=-8
q=-2
a₁=-3
a₂=-3*(-2)=6
a₃=6*(-2)=-12
a₄=-12*(-2)=24
a₄=24=-3*q³
q³=-8
q=-2
a₁=-3
a₂=-3*(-2)=6
a₃=6*(-2)=-12
a₄=-12*(-2)=24
annabeu:
Você pode me ajudar nesta questão também
respondido por:
19
Boa tarde!
Dados:
a1 → -3
an → 24
n → 2+2 = 4 ( Dois existentes mais dois que serão adicionados)
q → ?
___________
An=a1·q⁽ⁿ⁻¹⁾
24=-3·q⁽⁴⁻¹⁾
24=-3·q³
24/-3=q³
-8=q³
q=³√-8
q=-2
___________
P.G→ (-3, 6, -12, 24)
___________
Att;Guilherme Lima
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás